Cities As Built and Lived Environments - Khanbaghi, Aptin (Muslim Civilisations Abstracts EUP., 2014)
These 200 abstracts, in English, Arabic and Turkish, showcase scholarship that examines cities as built (architecture and urban infrastructure) and lived (urban social life and culture) environments.